2022
DOI: 10.3390/f13091364
|View full text |Cite
|
Sign up to set email alerts
|

Web-Based Communication of Wooden Sport Equipment: An Analysis Based on Six Olympic Sports

Abstract: Wood has traditionally been used to make sports equipment and playing surfaces. While its use is outdated in several sports, in many others, wood remains well-established or even the material of choice, e.g., to make basketball floors or table tennis rackets. This study aims at evaluating the main drivers of web-based communication of wooden sport equipment. Six Olympic sports in which wood is still used were identified: baseball, skateboarding, skiing, snowboarding, surfboarding, and table tennis. For each sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 35 publications
(33 reference statements)
0
4
0
Order By: Relevance
“…For instance Ref. [ 29 ], have recently shown that several sport companies have been heavily focusing their brand awareness and marketing strategies on environmental sustainability.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance Ref. [ 29 ], have recently shown that several sport companies have been heavily focusing their brand awareness and marketing strategies on environmental sustainability.…”
Section: Resultsmentioning
confidence: 99%
“…[ 28 ], the market analysis report of reference for the acoustic guitar industry. We analyzed the websites of the world's 14 major acoustic guitar manufacturing companies, as website analysis is recognized as an effective method for assessing product features also in the wood sector [ 29 ]. One website was excluded that is available in Chinese only, to avoid the risk of acquiring inaccurate data due to translation issues.…”
Section: Methodsmentioning
confidence: 99%
“…Investing in enhancing the synergy between the "tradition of chestnut use" and "vocational training initiatives" could play a strategic role [64]. Traditional knowledge, skills, and practices, combined with new training activities, could steer production and marketing towards innovative processes and products [65]. Such process has the potential to convert competition from foreign standard assortments into an advantage based on supply differentiation (e.g., switching from marketing raw and semi-finished wood to labelled finished products with higher added value).…”
Section: Discussionmentioning
confidence: 99%
“…Investing in enhancing the synergy between the "tradition of chestnut use" and "vocational training initiatives" could play a strategic role (Lingua et al, 2019). Traditional knowledge, skills and practices, combined with new training activities, could steer production and marketing towards innovative processes and products (Negro et al, 2022). Such process has the potential to convert competition from foreign standard assortments into an advantage based on supply differentiation (e.g., switching from marketing raw and semi-finished wood to labelled finished products with higher added value).…”
Section: Discussionmentioning
confidence: 99%